Diguanylate cyclase Dgc1 synthesizes c-di-GMP and modulates WL gum exopolysaccharide production in Sphingomonas sp. WG - Hui Li; Yanhui Jia; Hangxu Liu; Zaimei Zhang; Mengqi Chen; Huiyu Zheng; Mengqing Xu; Mengmeng Zang; Dong Wang; Yawei Sun; Hu Zhu; Jiqian Wang (Bioresource Technology, 2026)

High-coverage paleo-genome research identifies a pathogenic mutation on EXT1 in a Qing-period Chinese individual with multiple osteochondromas - Bangyan Wang; Haodong Chen; Fanhao Xi; Haoquan Bao; Hetong Wen; Panxin Du; Chenshuang Sun; Jianxue Xiong; Baoshuai Zhang; Xin Chang; Yawei Zhou; Chuan-Chao Wang; et al. (Molecular Genetics and Genomics, 2026)

Structure-activity relationship and salinity-driven degradation pathway and toxicity divergence of bromophenols during advanced reduction in VUV/sulfite system - Yawei Shi; Keyan Liu; Yan Wang; Ya Sun; Zonglin Pan; Mengqi Li; Guanghui Ding (Journal of Water Process Engineering, 2026)

Anti-melanogenic bioactive peptides: Molecular mechanisms, source, preparation, structural optimization and cross-field prospective application - Qun Yu; Haozhe Li; Yanxia Sun; Yawei Yu (Trends in Food Science & Technology, 2026)

N and S co-doped graphene-based single-atom catalysts for highly efficient nitrate reduction - Jin-Hang Liu; Yu Sun; Xiaoduo Jiang; Huixiong Jiang; Ruirui Wang; Yawei Wang; Huixian Ye; Xiudong Chen; Li-Ming Yang (Fuel, 2026)

Notable impact of urban ventilation corridors on the transport of particle-bound ultrashort-chain perfluoroalkyl substances in the atmosphere - Anen He; Feifei Li; Juan Li; Fanghan Sun; Han Fang; Xu Sun; Yanli Guo; Hailin Wang; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2026)

HILPDA, Regulated by WTAP in an m6A-Dependent Manner, Enhances Osteosarcoma Development by Inhibiting Ferroptosis and Promoting Glycolysis - Yong Jing; Guoyong Zhang; Chenghui Sun; Yawei Pan; Jun Tuo; Zhi Li; Chengji Jiang; Zejian Qiu; Qin Lou (Biochemical Genetics, 2026)

Oxidative carbothermal reduction for preparation of high-loading nano-zero-valent iron doped biochar for removal of tetracyclines and fluoroquinolones - Ahui Sun; Hongru Jiang; Yawei Xiao; Jihui Li (Journal of Environmental Chemical Engineering, 2026)

Injectable self-healing hydrogel for co-delivery of stem cells and growth factors in intervertebral disc regeneration - Zhiming Tu; Weichu Sun; Tao Yuan; Yuliang Dai; Xiaoya Ding; Yawei Li; Xiaocheng Wang; Bing Wang (Chemical Engineering Journal, 2026)

Charge-tuning via Al3+-induced between vanadium-oxide layers for robust aqueous zinc-ion batteries - Keli Duan; Ahui Sun; Yawei Xiao; Hongru Jiang; Zhonghua Bao; Xiufen Ma; Jihui Li (Chemical Engineering Journal, 2026)

Human thermal responses to non-uniform cooling from intermittently operated split air conditioners - Haiyan Yan; Yawei Li; Thomas Parkinson; Stefano Schiavon; Hui Zhang; Ruiji Sun; Shengkai Zhao; Wei Zhao; Zhen sun; Fangning Shi (Building and Environment, 2026)

Parental HFPO-TA exposure induces intergenerational reproductive toxicity and DNA methylation alterations in zebrafish - Shasha Dong; Xiaohui Zhao; Xuan Ren; Jing Zhang; Zhibo Liu; Dan Yang; Ning Ji; Yawei Shi; Ya Sun; Guanghui Ding (ENGINEERING Environment, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Applications of machine learning-based quantitative structure activity relationship (ML-QSAR) models in environmental science - Chao Chen; Yujia Tan; Yawei Liu; Miaomiao Sun; Zhiquan Wang; Xiangyong Zheng; Zhemin Shen; Min Zhao (Environmental Research, 2026)

Chloride Loss in Fine Aerosols over the Atmosphere of Pearl River Estuary - Yuan Gao; Jianbo Ye; Lili Ming; Run Lu; Jiayin Sun; Guizhen Fang; Yawei Xue; Yee Jun Tham (Aerosol Science and Engineering, 2026)

Invertible neural network for real-time inversion and uncertainty quantification of ultra-deep resistivity measurements - George Bittar; Sihong Wu; Yawei Su; Shubin Zeng; Jiajia Sun; Xuqing Wu; Yueqin Huang; Jiefu Chen (Computers & Geosciences, 2026)

An exergy-guided thermodynamic framework for the optimization of electro-membrane-based coupled process - Ruochen Shen; Yawei Du; Lurong Wang; Mengmeng Sun; Tianyi Chen; Shizhao Wang; Jingtao Bi; Wenhao Li; Jianlu Liu; Yingying Zhao (Water Research, 2026)

Performance analysis of seismic mitigation by replacing foundation soil with a periodic structure for nuclear power structures considering SSI - Zequan Sun; Yawei Duan; Mi Zhao; Zhidong Gao; Di Yao; Lihua Wu; Guoliang Zhang; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2026)

Anthropogenic filtering of detrital zircon and rutile signals in the Yangtze River: Implications for provenance reconstruction - Rujun Guo; Xianyan Wang; Xilin Sun; Wencke Wegner; Zengjie Zhang; Yawei Li; Chuanyi Wei; Taorui Zeng; Urs Klötzli; Chang'an Li (Global and Planetary Change, 2026)

Cardiac targeted delivery of Maresin 1 nanomedicine rescues microvascular obstruction after myocardial infarction - Yawei Zhao; Jing Zhang; Xiaohan Fan; Yue Cai; Wenting Du; Ziyi Yu; Biao Xu; Xuan Sun (Chemical Engineering Journal, 2026)

Involvement of two-component system CseB-C in differential regulation of rapamycin and elaiophylin biosynthesis in Streptomyces rapamycinicus - Yawei Zhao; Shangping Jin; Pan Wang; Yuan Wang; Na Liu; Aimei Liao; Zhe Sun; Yinhua Lu; Hailong Tian (Food Bioscience, 2025)

Reversibility of the reproductive toxicity induced by hexafluoropropylene oxide trimer acid (HFPO-TA) in adult zebrafish (Danio rerio) - Dan Yang; Xuan Ren; Xiaohui Zhao; Shasha Dong; Xiaoying Li; Yawei Shi; Ya Sun; Guanghui Ding (Aquatic Toxicology, 2025)

Microbial-mediated transformation shapes the molecular diversity of landfill leachate under anthropogenic and natural covariation - Qiurui Zhang; Jitao Lv; Shiyang Yu; Tianyu Chen; Yue Sun; Feifei Li; Lu Bai; Xianwei Wang; Xiaosong He; Yong Nie; Nanwen Zhu; Yawei Wang; et al. (Water Research, 2025)

A general pyrolysis strategy to construct rare-earth oxide-stabilized high-density Ru single atom catalysts for efficient thermocatalytic CO2 methanation - Yunxiang Tang; Yanan Zhang; Aihuan Sun; Hao Wang; Yawei Miao; Zhengyi Yang; Yunqian Tang; Qun Li; Shujiao Wang; Lingheng Kong; Yinfeng Han (Chemical Engineering Journal, 2025)

Preparation of nano zero-valent iron-doped magnetic biochar from different types of iron salts: Comparing their adsorption capability for sulfamethoxazole - Kaili He; Ahui Sun; Zijing Guo; Chonglin Zheng; Yujie Jin; Hongru Jiang; Yawei Xiao; Jihui Li (Journal of Environmental Chemical Engineering, 2025)

Seismic response and failure mode of a subway station in a ground fissure area - Xuan Chen; Yawei Wu; Hongquan Teng; Zhongming Xiong; Qiren Sun; Yan Zhuge (Earthquake Engineering and Engineering Vibration, 2025)

Stem nematode disease resistance-conferring gene identification in sweet potato using combined BSA-Seq and BSR-Seq analyses - Shouchen Qiao; Jingwei Chen; Yawei Li; Yannan Wang; Jukui Ma; Zhihe Kang; Qianqian Bian; Guozheng Cao; Guorui Zhao; Guohong Yang; Yanping Fan; Houjun Sun; et al. (Planta, 2025)

MnFe2O4 coupled with MgAl-LDH for activation of periodate towards enhanced degradation of organic pollutants in water - Ya Sun; Chang Ma; Yawei Shi; Zonglin Pan; Yumei Xing; Yan Wang; Keyan Liu; Guanghui Ding (Journal of Water Process Engineering, 2025)

Pt-CeO2/SDB ternary structure achieved by modulating electronic interaction for high-efficiency toluene oxidation - Zun Liu; Guotan Liu; Xuanye Liu; Weihong Gao; Yudong Fu; Bin Sun; Yawei Shao; Guojun Dong (Journal of Environmental Chemical Engineering, 2025)

A novel N/C co-modified FeS2 nanocomposite synthesized by wet-mechanochemical method for efficient peroxymonosulfate activation and nearly 100% SO4•─ selective generation - Longquan Zhang; Guangfei Gao; Xiaoguo Shi; Zunqing Wen; Minglu Zhang; Qingyun Wang; Qing Feng; Jing Sun; Xuezheng Liu; Ying Zhao; Yawei Gu; Wenqiang Jiang (Chemical Engineering Journal, 2025)

Characterization and Assessment of Sheep-Origin Probiotic Bacillus licheniformis B63 Strain for Potential Use in Intestinal Health and Disease - Meng Hou; Yabin Lu; Mengjun Ye; Na Li; Yawei Sun; Gang Yao; Jinquan Wang; Fangfang Yin; Qimin Peng; Sheng Jia; Rui Shi; Xuxiang Wang (Probiotics and Antimicrobial Proteins, 2025)

Research on multi-objective control algorithm for micro-nano satellite formation based on array signal detection - Jiao Wang; Boao Zhu; Chengshang Li; Chong Sun; Yawei Wan (Advances in Space Research, 2025)

Nonlinear dynamic analysis of a 3D land-fixed oscillating water column wave energy converter - Dezhi Ning; Yawei Sun; Rongquan Wang; Peiwen Cong (Ocean Engineering, 2025)

Efficient Degradation of Organic Pollutants by Activation of Sodium Percarbonate with CuFeS2 Catalytic Membrane - Yawei Shi; Yumei Xing; Qian Chang; Ya Sun; Guanghui Ding (Water, Air, & Soil Pollution, 2025)

Titanium-based hollow fiber membrane: Fabrication, optimization, and electrochemical filtration treatment performance - Xiaoqing Yan; Zonglin Pan; Xinyuan Zhou; Shuo Liu; Hang Yu; Ruisong Xu; Yawei Shi; Xinfei Fan; Tianjun Sun; Yongxin Song; Chengwen Song (Journal of Environmental Chemical Engineering, 2025)

The individualized optimal pillow height and neck support design for side sleepers - Shan Tian; Chenghong Yao; Yawei Wang; Xuepeng Cao; Yike Sun; Lizhen Wang; Yubo Fan (Medical & Biological Engineering & Computing, 2025)

Lovastatin enhances humoral and cellular immune responses to H1N1 influenza vaccine - Zuchen Song; Yantong Zhou; Lina Jiao; Tianyu Zhu; Ruihong Yu; Zheng Wang; Yawei Qiu; Jinfeng Miao; Ting Cai; Shun Zhang; Huina Liu; Haifeng Sun; et al. (Veterinary Microbiology, 2025)

Degradation of aqueous organic pollutants by dual oxidant advanced oxidation processes: A comprehensive review - Yawei Shi; Yumei Xing; Chang Ma; Ya Sun; Guanghui Ding (Journal of Environmental Chemical Engineering, 2024)

Further geochronological constraints on the Xiuyan impact crater in northeast China - Zeyang Zhu; Chang Huang; Jing Wu; Yawei Li; Zhihao Sun; Min Zhang; Bin Zhang; Sheng-Hua Li; Jiaqi Liu (Frontiers of Earth Science, 2024)

Molecular designing of potential environmentally friendly PFAS based on deep learning and generative models - Ying Yang; Zeguo Yang; Xudi Pang; Huiming Cao; Yuzhen Sun; Ling Wang; Zhen Zhou; Pu Wang; Yong Liang; Yawei Wang (Science of The Total Environment, 2024)

CoAl-Layered Double Hydroxide Catalytic Membrane for Activation of Peroxymonosulfate Towards Efficient Degradation of Organic Pollutants - Yawei Shi; Tongwen Zhang; Qian Chang; Zonglin Pan; Ruisong Xu; Ya Sun; Guanghui Ding (Water, Air, & Soil Pollution, 2024)

Prevalence of antibiotic resistance genes, heavy metal, and bacterial community composition in sea sediments influenced by Eriocheir sinensis breeding aquaculture - Hui Fu; Wei Sun; Yawei Cao; Qing Li; Xiaotong Wang; Zijie Zhou; Qian Meng; Tingyi Luo; Wei Gu; Qingguo Meng (Environmental Science and Pollution Research, 2024)

A review of the pollution signatures of polycyclic aromatic hydrocarbons in the sediments of the East China Sea - Fang Yin; Chen Gao; Daolun Feng; Yawei Sun (Environmental Pollution, 2024)

Hollow engineering of Co/N-doped C@carbon aerogel with hierarchical structure boosting interfacial polarization for ultra-thin microwave absorption and thermal insulation - Panpan Zhou; Shiyu Zhang; Wei Zhou; Chencheng Sun; Chengyao Hu; Shilin Yuan; Jiarui Li; Chang Liu; Yuchen Zhao; Yawei Kuang; Shuchang Wang; Qitu Zhang; et al. (Chemical Engineering Journal, 2024)

Thyroid disrupting effects and the developmental toxicity of hexafluoropropylene oxide oligomer acids in zebrafish during early development - Xiaohui Zhao; Xianghan Meng; Dan Yang; Shasha Dong; Jianhui Xu; Dezhi Chen; Yawei Shi; Ya Sun; Guanghui Ding (Chemosphere, 2024)

Linking the removal of enrofloxacin to the extracellular polymers of microalgae in water bodies: A case study focusing on the shifts in microbial communities - Youyin Hu; Shangsheng Sun; Xuewei Gu; Ziyi Li; Jialin Zhang; Yawei Xing; Liqing Wang; Wei Zhang (Environmental Science and Pollution Research, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Rutile and zircon U-Pb dating as a constraint on sedimentary provenance of the Jianchuan Basin: Implications for paleo-drainage evolution - Rujun Guo; Xilin Sun; Chang'an Li; David Chew; Foteini Drakou; Zengjie Zhang; Yawei Li; Chuanyi Wei; Taorui Zeng; Jiranan Homnan; Urs Klotzli (Geomorphology, 2024)

Assessment major NOx sources to nitrate of TSP around the Danjiangkou reservoir using isotopes and a Bayesian isotope mixing model - Chunyan Xiao; Yimeng Sun; Tongqian Zhao; Guizhen Wang; Pengbo Li; Yawei Zhao; Feihong Chen (Atmospheric Pollution Research, 2024)

Efficient degradation of organic pollutants with sodium percarbonate by activation with CuFeS2 prepared from precursors of different valence states - Yawei Shi; Qian Chang; Tongwen Zhang; Zonglin Pan; Ruisong Xu; Ya Sun; Guanghui Ding (Journal of Environmental Chemical Engineering, 2024)

Associations of environmental cadmium exposure with kidney damage: Exploring mediating DNA methylation sites in Chinese adults - Yuan Wei; Xiaochen Wang; Qi Sun; Wanying Shi; Wenli Zhang; Xu Gao; Yawei Li; Ruiting Hao; Xiaojie Dong; Chen Chen; Kangning Cao; Weilong Jiang; et al. (Environmental Research, 2024)

Photo-Enhanced Lead-Free Antimony-Based perovskite triboelectric nanogenerator for Dual-Mode detector - Ling Ding; Zhan Wei; Na Sun; Yawei Cai; Yanhong Zhou; Kan Fang; Guigen Wang (Chemical Engineering Journal, 2024)

A dual-emitting fluoroprobe fabricated by aloe leaf-based N-doped carbon quantum dots and copper nanoclusters for nitenpyram detection in waters by virtue of inner filter effect and static quenching principles - Junxia Wang; Yueying Sun; Panpan Wang; Zhengpeng Sun; Yawei Wang; Ming Gao; Huili Wang; Xuedong Wang (Analytica Chimica Acta, 2024)

Efficient removal of organic pollutants by activation of peroxydisulfate with the magnetic CoFe2O4/carbon nanotube composite - Yawei Shi; Yi Zhang; Guobin Song; Ya Sun; Guanghui Ding (Environmental Science and Pollution Research, 2023)

Micro-algal astaxanthin ameliorates polystyrene microplastics-triggered necroptosis and inflammation by mediating mitochondrial Ca2+ homeostasis in carp’s head kidney lymphocytes (Cyprinus carpio L.) - Lei Diao; Meiqi Ding; Hongzhen Sun; Yawei Xu; Rui Yin; Huijie Chen (Fish & Shellfish Immunology, 2023)

Experimental investigation on a novel and hyper-efficient oscillating water column wave energy converter coupled with a parabolic breakwater - Robert Mayon; Dezhi Ning; Yawei Sun; Zhenyu Ding; Rongquan Wang; Yu Zhou (Coastal Engineering, 2023)

Experimental research on the flame resistance characteristics of wire mesh for syngas explosion - Xingyan Cao; Zhi Wang; Zhirong Wang; Yawei Lu; Shaochen Sun; Jianjun Xu (Process Safety and Environmental Protection, 2023)

Distribution characteristics of photoinitiators and their flux estimation from the Pearl River Delta to the coastal waters of the South China Sea - Yuqing He; Zibin Pan; Xinxin Liang; Ruiman Xie; Yuying Sun; Juan Li; Yawei Wang; Lixi Zeng (Journal of Environmental Sciences, 2023)

Reinforcing supramolecular hyaluronan hydrogels via kinetically interlocking multiple-units strategy - Ruofan Chen; Yujie Li; Yu Jin; Yawei Sun; Zhiyong Zhao; Yun Xu; Jiang-Fei Xu; Yuanchen Dong; Dongsheng Liu (Carbohydrate Polymers, 2023)

Facile Fabrication of Amino Functionalized Magnetic Multi-walled Carbon Nanotubes for Removal of Congo Red from Aqueous Solutions - Guobin Song; Liya Tong; Shuhua Chen; Jing Zhang; Yi Zhang; Haonan Wang; Yawei Shi; Ya Sun; Guanghui Ding (Water, Air, & Soil Pollution, 2022)

Numerical Investigation on Higher-Order Harmonic Waves Induced by a Submerged Inclined Plate - Zhimin Zhou; Yawei Sun; Lifen Chen; Dezhi Ning; Sulisz Wojciech (Journal of Marine Science and Engineering, 2022)
In this paper, a two-dimensional time-domain numerical flume has been established to model and investigate nonlinear interactions between nonlinear surface waves and a submerged inclined thin plate. The model solves the Laplace equation and the fully nonlinear free surface boundary conditions within the framework of potential flow theory based on the high-order boundary element method. The mixed Euler–Lagrangian method is applied to update the water surface at each time step, and the fourth-order Runge–Kutta method for time stepping. A so-called four-point method was employed to separate the second-order harmonic free and bounded wave that has the same wave frequency but different wave celerity in front of and behind the submerged plate. It is found that the amplitude of the second-order harmonic free wave increases with the inclination angle of the submerged plate, and the level/amount of the increase is larger for a larger wave steepness. In addition, the amplitudes of both the second-order reflected and transmitted waves are found to increase with the wave steepness, and their empirical relationships are derived for potential use in practical engineering.

MiR-128-3p Attenuates the Neurotoxicity in Rats Induced by Isoflurane Anesthesia - Duo Qian; Shijie Dai; Yujing Sun; Yawei Yuan; Long Wang (Neurotoxicity Research, 2022)

Magnetic graphene oxide for methylene blue removal: adsorption performance and comparison of regeneration methods - Yawei Shi; Haonan Wang; Guobin Song; Yi Zhang; Liya Tong; Ya Sun; Guanghui Ding (Environmental Science and Pollution Research, 2022)

Variations of human cerebral and ocular blood flow during exposure to multi-axial accelerations - Weipeng Li; Bitian Wang; Yawei Wang; Xiaoyu Liu; Wentao Feng; Tianya Liu; Zhujun Sun; Yu Liu; Songyang Liu; Yubo Fan (Medical & Biological Engineering & Computing, 2022)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Preconception ambient temperature and preterm birth: a time-series study in rural Henan, China - Guoyu Zhou; Meng Yang; Jian Chai; Renjie Sun; Junxi Zhang; Hui Huang; Yawei Zhang; Qihong Deng; Lifang Jiang; Yue Ba (Environmental Science and Pollution Research, 2021)

Multiplex genome editing using a dCas9-cytidine deaminase fusion in Streptomyces - Yawei Zhao; Jinzhong Tian; Guosong Zheng; Jun Chen; Chuanwen Sun; Zhongyi Yang; Andrei A. Zimin; Weihong Jiang; Zixin Deng; Zhijun Wang; Yinhua Lu (Science China Life Sciences, 2020)

Antimicrobial Peptide JH-3 Effectively Kills Salmonella enterica Serovar Typhimurium Strain CVCC541 and Reduces Its Pathogenicity in Mice - Lei Wang; Xueqin Zhao; Xiaojing Xia; Chunling Zhu; Wanhai Qin; Yanzhao Xu; Bolin Hang; Yawei Sun; Shijun Chen; Huihui Zhang; Jinqing Jiang; Jianhe Hu; et al. (Probiotics and Antimicrobial Proteins, 2019)

5-FU preferably induces apoptosis in BRAF V600E colorectal cancer cells via downregulation of Bcl-xL - Tongfei Shi; Mohan Gao; Meihui He; Fengli Yue; Yawei Zhao; Madi Sun; Kan He; Li Chen (Molecular and Cellular Biochemistry, 2019)

Population susceptibility differences and effects of air pollution on cardiovascular mortality: epidemiological evidence from a time-series study - Mengyao Liu; Xiaoxia Xue; Baosen Zhou; Yawei Zhang; Baijun Sun; Jianping Chen; Xuelian Li (Environmental Science and Pollution Research, 2019)

Proteomic survey towards the tissue-specific proteins of mouse mitochondria - Yuan Wang; HaiDan Sun; YaWei Ru; SongYue Yin; Liang Yin; SiQi Liu (Science China Life Sciences, 2011)